Acquisition and adaptation of the airway microbiota in the early life of cystic fibrosis patients - Boutin, Sébastien; Dalpke, Alexander (Molecular and Cellular Pediatrics, 2017)
Cystic fibrosis (CF) is a genetic disease in which bacterial infections of the airways play a major role in the long-term clinical outcome. In recent years, a number of next-generation sequencing (NGS)-based studies aimed at deciphering the structure and composition of the airways’ microbiota. It was shown that the nasal cavity of CF patients displays dysbiosis early in life indicating a failure in the first establishment of a healthy microbiota. In contrast, within the conducting and lower airways, the establishment occurs normally first, but is sensitive to future dysbiosis including chronic infections with classical pathogens in later life. The objective of this mini-review is to give an update on the current knowledge about the development of the microbiota in the early life of CF patients. Microbial acquisition in the human airways can be described by the island model: Microbes found in the lower airways of CF patients represent “islands” that are at first populated from the upper airways reflecting the “mainland.” Colonization can be modeled following the neutral theory in which the most abundant bacteria in the mainland are also frequently found in the lower airways initially. At later times, however, the colonization process of the lower airways segregates by active selection of specific microbes. Future research should focus on those processes of microbial and host interactions to understand how microbial communities are shaped on short- and long-term scales. We point out what therapeutic consequences arise from the microbiome data obtained within ecological framework models.